Determining the threonine requirement of the lactating sow - Schneider, J.D.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 182 lactating sows were used in a study to determine the threonine requirement, and the relative difference in resulting performance of lactation diets with high concentrations of crystalline amino acids, compared with a conventional corn-soybean meal diet. All experimental diets were based on corn-soybean meal and formulated to contain 0.88% true ileal digestible (TID) lysine (1.00 and 0.97% total lysine for the control treatment and crystalline amino acid treatments, respectively). The control treatment was a conventional corn-soybean meal diet with no added crystalline amino acids. The other five experimental diets contained 0.37% L-lysine HCl, with other amino acids added to ensure that threonine was first limiting. The TID threonine contents in these diets were formulated to 0.44, 0.50, 0.57, 0.64, and 0.70%. Sows were farrowed in seven farrowing groups and were randomly allotted to the dietary treatments on the basis of parity. Over the entire lactation period, sows fed the diets containing crystalline amino acids consumed more (P<0.04) feed than did the sows fed the control corn-soybean meal diet. The sows fed the control diet also lost numerically (P>0.10) more weight over the lactation period. Sows fed the control diet had higher (P<0.01) PUN values at day 18 of lactation than did sows fed diets with added crystalline amino acids. There was no effect (P>0.10) on litter weaning weight with increasing dietary threonine. The numeric changes in PUN, litter weight gain, and feed intake suggest that the TID threonine requirement was 0.50%, which calculated to a threonine-to-lysine ratio of 57%. But the greatest implication of this study was that the use of crystalline amino acids as a replacement for soybean meal in lactation diets resulted in increased feed intake and decreased sow weight loss.
Swine research, 2005 is known as Swine day, 2005
Keywords: Swine; Crystalline amino acids; Lactation; Sows; Threonine